Cassava Peel - Cowpea Hull Blended Agro-Waste Fillers: Effect on Mechanical, Morphological and Degradation Properties of Polypropylene (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: This study is aimed at harnessing the effect of cassava peel and cowpea hull blended agro-waste on the mechanical, morphological and degradation properties of polypropylene and recycled polypropylene. Fine powders of mesh size of 75µm cassava peel and cowpea hull were homogeneously mixed at the ratio of 50:50 to form the hybrid filler. The virgin pellets of PP and recycled polypropylene (rPP) were filled with varying weight percentages (5, 10, 15, 20) of the blended filler and the composites produced via injection moulding technique. The mechanical properties; tensile strength, percentage elongation at break, hardness, compressive strength, and shear modulus were studied according to American Society for Testing and Materials (ASTM) standards. The morphological properties were studied with a Scanning Electron Microscope at 10,000 magnifications. The degradation study was achieved by soil burial method for one hundred and eighty (180) days period. The results of the mechanical properties showed increased tensile strength, hardness, compressive strength and shear modulus while the percentage elongation at break decreased as the filler load increases. The micrographs showed that the virgin PP has better adhesion and interfacial bonding with the filler than the rPP. Biodegradation test revealed a reduction in the mass of the composites after one hundred and eighty (180) days burial period indicating that the composite is degradable. From the findings, the cassava peel-cowpea hull blended filler can be used in materials where stiffness and strength is required. Hence, it is suggested that agro-wastes such as cassava peel and cowpea hulls could be used as fillers in production of degradable plastics as they are readily available, cheap and easy to use.